Prevalence of home smoking bans in six European cities: a repeated cross-sectional study (2013-2016). (13th November 2019) - Anastasi, D; Federico, B; Rimpela, A; Richter, M; Clancy, L; Perelman, J; Kunst, A E; Lorant, V
Abstract: Background: Secondhand smoke exposure is responsible for over half a million premature deaths. With regulation now reducing smoking in most public enclosed spaces, one major source of indoor exposure remains the home environment. Home smoking bans (HSBs) are household rules that restrict smoking from certain (partial HSB) or all areas (complete HSB). Recent data suggest growing trends of HSB adoption over time, but it is not known whether time trends vary according to household characteristics. Objectives: The aim of this study is to examine changes in the prevalence of HSB in six European cities between 2013 and 2016, according to socioeconomic characteristics of the household and smoking behavior of household members. Methods: Data were collected in all schools participating in both waves of SILNE study in 6 European cities. A self-administered questionnaire was used, targeting students age 14 to 16 (n = 22, 326). Students reported their parents' smoking status and if there was a HSB at their home. Detailed information on socio-economic characteristics were collected as well. Results: Between 2013 and 2016 the percentage of households with a complete HSB increased from 51.5% to 53.1%, while partial HSB increased from 30.7% to 32.1%. The prevalence of HSB increased in Hannover (G), Latina (I), Amersfoort (N) and Coimbra (P), whereas decreased in Namur (B) and Tampere (F). Socioeconomic differences in HSB were reduced, with larger increases in HSB in households with a lower parental educational level. Increases in HSB were observed among intact households, those without migration background and those with non-smoking parents. Conclusions: The increase in the prevalence of HSB observed in most cities and throughout a variety of household types and characteristics between 2013 and 2016 may reflect the effect of smoking denormalization in different social contexts. Further actions of the tobacco control community should target the most vulnerable groups. Key messages: The percentage of households with a complete HSB increased between 2013 and 2016 in 4 out of 6 European cities. Increases in the prevalence of HSB over time were observed across all socio-economic groups.